Psychological Dimensions in Sayed Qutb's Novel 'Ashwak' (Thorns) (The International Journal for Scientific Research, 2024)
This study examines the novel "Thorns" by Sayed Qutb, published in 1947, as a personal narrative reflecting a real experience that Sayed lived in his private life, particularly focusing on the emotional dimensions stemming from this experience. The study investigates the significance of the title, which faithfully reflects the text, the events of the novel and its structure in light of psychological methodology, the nature of the characters and their internal conflicts, the psychological trajectory of the protagonist and the heroine, the structure of place and time, analysis of artistic elements, and the artistic methods and techniques that often reveal a refined narrative sensibility and a complete awareness of the creative process.
Keywords: Psychological Methodology; Sayed Qutb; Autobiographical Novel